2002
DOI: 10.1002/tl.44
|View full text |Cite
|
Sign up to set email alerts
|

Successful Lecturing: Presenting Information in Ways That Engage Effective Processing

Abstract: An effective lecture—one that induces effective processing in one's students—can be a successful method of teaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 48 publications
0
41
0
3
Order By: Relevance
“…Similarly, recognition of nine-digit strings an hour after study was more than twice as high for subjects who verbally repeated the strings after presentation than for subjects who passively observed the strings (Glass, Krejci, & Goldman, 1989). The general phenomenon of improved retention as a result of actively producing information is known as the 'generation effect' (Slamecka & Graf, *Email: aglass@rutgers.edu 1978), and has become one of the most robust findings emerging from the laboratory study of learning (deWinstanley & Bjork, 2002). Importantly, Foos, Mora, and Tkacz (1994) showed that the generation effect can be found in natural educational settings for material specifically targeted by students' generated outlines and questions.…”
mentioning
confidence: 94%
“…Similarly, recognition of nine-digit strings an hour after study was more than twice as high for subjects who verbally repeated the strings after presentation than for subjects who passively observed the strings (Glass, Krejci, & Goldman, 1989). The general phenomenon of improved retention as a result of actively producing information is known as the 'generation effect' (Slamecka & Graf, *Email: aglass@rutgers.edu 1978), and has become one of the most robust findings emerging from the laboratory study of learning (deWinstanley & Bjork, 2002). Importantly, Foos, Mora, and Tkacz (1994) showed that the generation effect can be found in natural educational settings for material specifically targeted by students' generated outlines and questions.…”
mentioning
confidence: 94%
“…Ironically, a few weeks ago, seemingly out of the blue, my son asked me, “Mom, which is the most important – the past, the present, or the future?” After a few seconds of thought, I responded, “The present.” Without hesitation he said “That's right, because it's the only one of the three you can do anything about.” How true, I thought. Research tells us that there are a myriad of positive outcomes associated with “living in the present” (similar terms include mindfulness and attentiveness) such as promoting personal health and well‐being, enhancing interpersonal relationships (Brown and others ), and improving memory (deWinstanley and Bjork ). Being present is key to making the most of the present, which should, theoretically, also benefit the future.…”
Section: Being Presentmentioning
confidence: 99%
“…Learning during lecture, on the other hand, implies that something special is happening during lecture. As discussed by deWinstanley and Bjork (), “…achieving such a goal [learning during lectures] requires that lectures trigger in students the types of processes that result in durable encoding of the concepts, facts, and ideas covered in the lecture—encoding of the type that will survive beyond the lecture period. Ideally, we would also like students to acquire a mental representation of the to‐be‐acquired knowledge that allows for flexible access to that knowledge—that is, the ability to generalize.” (p. 20).…”
Section: Learning During Lecturementioning
confidence: 99%
“…My preference is towards the use of complete notes, as my belief is that they are better suited to computer science, due the propensity towards incorporating programming examples, figures, and reference material in the notes. The onus on students to capture a complex figure or code-segment in their notes can detract from their ability to sustain focused attention [5], and hence participate in the active learning process. Hartley [7] observed that the amount of space provided for note taking directly influences the amount of notes taken.…”
Section: The Practice Of Using E-notesmentioning
confidence: 99%